The struggle for health medicine and the politics of underdevelopment - Sanders, David 1945-2019 (Oxford University Press, 2023)
The first edition of The Struggle for Health was published in 1985 and was widely acclaimed by those seeking a broader and deeper political understanding of ill health, beyond the medical model of care. It was a revolutionary book, charting new ways of understanding and tackling the causes of ill health, and suggesting strategies to enable health for all. This second edition includes health problems that have emerged since the 1980s, notably HIV/AIDs, COVID-19, and other epidemics, and the increase in non-communicable diseases, such as cardiovascular disease and diabetes. It examines some of the health impacts of globalization, specifically on the food and pharmaceutical value chains, and considers the consequences of climate change on the health of populations. However, this edition does not depart from the core message of the original book: Health for All can only be achieved through a more equitable distribution of wealth, resources, and power. The Struggle for Health, Second Edition, utilises the same approach as the first, with a narrative that begins with diseases, then describes historical trends and the limitation of the medical (and commercial) model of care. At each juncture, it asks the question 'WHY' - why do people, especially children, still die in large numbers throughout the world, from wholly preventable diseases? Why is it that appropriate provision for health care is not available to every individual in the world? What changes can be made to improve this situation? Most importantly, this edition presents a strengthened call to action, building upon the original work and advocating for systemic changes to ensure justice and equity in health for all